Angel Investors and Startups: An Analysis: The Role of Angel Investors in Startup Funding and the Need for Regulatory Clarity (Journal of Advances and Scholarly Researches in Allied Education, 2020)
For start-up companies, angel investors are a critical source of capital, with many relying on them for a major amount of their total funding. Angel investors are the most important source of external funding for emerging enterprises, behind founders, family members, and close friends, among other sources. Angel investment may it be individually or collectively as angel networks are very beneficial for the Startup environment. Startups need seed money to grow at initial stage and that is the reason angel investors are crucial for them. These investors are also helpful in initially managing the business because they are having experience. The article discusses about the process of angel investment and also suggest some very important aspects needs to be regulated by the authorities, for better clarity in Capital markets.